Obtenção de zonas de manejo para fertilidade e estoque de carbono no solo em áreas de pastagem, integração pecuária-floresta e eucalipto - Daniel Filho, Paulo (Universidade Federal de São Carlos, 2025)
The definition of management zones is a fundamental strategy to improve productive and environmental efficiency in agriculture. This study aimed to identify specific management zones for soil fertility and carbon stock, evaluating four different land use systems in the Cerrado of Goiás: monoculture pasture (P1), polyculture pasture (P2), livestock-forest integration (IPF) and eucalyptus silviculture (EM). A total of 996 soil samples were collected, 830 of which were destined for carbon analysis and 166 for fertility. The data were processed via geostatistical interpolation (ordinary kriging), using the spherical model, and standardized by fuzzy logic to generate thematic maps. The results revealed that the IPF presented the highest average value of CEC (3.28 cmolc dm⁻³) and base saturation (38.58%), while silviculture presented the lowest V% (25.81%). For phosphorus, forestry also stood out with the highest average (6.83 mg dm⁻³), and monoculture pasture presented the lowest values ​​in several attributes. A significant correlation was observed between soil fertility and carbon stock, with emphasis on the most fertile areas presenting higher C contents. The adopted methodology demonstrated effectiveness in defining differentiated management zones, promoting a more rational use of resources and contributing to sustainable agricultural practices adapted to local edaphoclimatic conditions.
Obtaining management zones for soil fertility and carbon stock in pasture areas, livestock-forest integration and eucalyptus
Keywords: Geoprocessamento; Agricultura de precisão; Sustentabilidade agrícola; Modelagem computacional; Variabilidade espacial; Geoprocessing; Precision agriculture; Agricultural sustainability; Computational modeling; Spatial variability; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO